High voltage direct current transmission - Arrillaga, J. (Institution of Engineering and Technology, 1998)
Since the first edition of this book in 1983, HVDC technology has continued to expand and few power systems can now escape its influence. This thoroughly revised text develops the coverage in the first edition, describing the variety of reasons justifying the use of DC transmission as well as the basic concepts and techniques involved in the AC-DC and DC-AC conversion processes. It has been fully updated and enlarged to include descriptions of the widening applications of DC, the current state-of-the-art thyristors and other semiconductor devices, and the new developments that continue to make HVDC a competitive technology. The book should be of interest to practising engineers and researchers involved in the power industry. It will also be of assistance to lecturers and students in the power systems and power electronics disciplines.